Analytical lifecycle management approach: Application to development of a reliable LC method for estimation of lacidipine. Issue 1 (25th January 2019) - Panda, Sagar Suman; Bera, Ravi Kumar Venkata Varaha; Acharjya, Sasmita Kumari; Sahoo, Padmalaya; Beg, Sarwar
Abstract: Lack of quality analytical methods with assured robustness and reliability has always been a serious concern for drug regulatory agencies. In the present study, a contemporary approach of analytical life‐cycle management resulted in the robust and reliable chromatographic analysis of lacidipine at a retention time of 5.1 min on a C‐18 column. Method variables such as %acetonitrile, flow rate, and pH were optimized using the design of experiment approach and their effect on critical quality attributes was studied. The attributes of the present study were significantly influenced by %acetonitrile and flow of the mobile phase. The newly optimized method was validated for various parameters with values in accordance with federal guidance. The lifecycle approach proved to be beneficial for routine application with a potential of future bio‐analytical utility.